EFEK ANTIOKSIDAN PEMBERIAN EKSTRAK PLASENTA DOMBA ORAL PADA TIKUS SPRAGUE DAWLEY: Efek Antioksidan Ekstrak Plasenta Domba - Siufui Hendrawan; Sukmawati Tansil Tan; Nuraeni; Meilani Kumala (Yayasan Pendidikan Medika Indonesia, 2022)
Sheep placental extract (SPE) has been widely consumed in several parts of the world, owing to its capability to enhance vitality and anti-aging activity. However, the biological mechanism and safety effect of SPE have not been robustly studied. Hence, this research aims to assess the antioxidant capacity and broad safety effect of the SPE. An experimental study was conducted on Sprague Dawley rats (n=9 male; n=9 female); randomly allocated into 3 groups (n=6). The control group received distilled water, low-dose group received 500 mg/kg BW of SPE, while high-dose group received 1000 mg/kg BW of SPE; 3 times a week for 1 month respectively. At endpoint, superoxide dismutase (SOD) activity was measured as the parameter of antioxidant capacity and histopathology staining was performed on several tissues: skin, liver, uterus, ovarium, testicle; using Haematoxylin Eosin staining to assess the SPE toxicity effect. As the result, the SOD activity increased in line with the SPE doses given. Although not statistically significant different compared with the control group (54.49±18.41 %inhibition rate), the highest mean SOD activity was found on high-dose group (64.30±9.21 %inhibition rate), while low-dose group had mean SOD activity of 61.60±14.69 %inhibition rate. The effect of SPE on SOD activity did not appear to cause significant differences between male and female rats. Histopathological examination did not show any abnormalities in skin, liver, or reproductive organs caused by the SPE. This study demonstrated that oral administration of SPE in rats could increase antioxidant capacity, although not significantly and did not exert any toxicity effect in general.